KARAKTERISTIK PERTUMBUHAN DAN PERKEMBANGAN SISWA SMP: PRINSIP DAN REKOMENDASI UNTUK PEMBELAJARAN PENDIDIKAN JASMANI - Yusup Hidayat (Jurnal Pendidikan Jasmani Indonesia, 2006)
Several things of the success indicators for the learning process of physical education areknowledge and deep understanding from the physical education teacher on characteristicsof the student’s growth and development. The physical education teacher’s understandingon those matters will contribute to the effectivity on choosing and determining activities tothe students. It also has more benefits in choosing and determining appropriate methodand strategy of learning. Several characteristics of growth and development that physicaleducation teachers should be aware are physical growth and development aspects, motorskill development, social-personality development, cognitive, emotion and moral.Keywords: characteristics of growth and development, physical education learning.